2004
DOI: 10.1080/00016480410016478
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prototyping of temporal bone for surgical training and medical education

Abstract: This prototype 3D model made using selective laser sintering serves as a good educational tool for middle ear surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 1 publication
0
79
0
2
Order By: Relevance
“…Surgical skills can be practiced on genuine or generic bone morphologies as reported, for example, in Otolaryngology, and maxillofacial and cranial reconstructive surgery. 4 Fracture simulations with 3D models 5 can already replace plastic bones for training of osteosynthesis as illustrated in Figure 3. Exercising preoperative planning on a generic 3D environment will permit the trainee to gain a more a comprehensive understanding of the pertinent bone's morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical skills can be practiced on genuine or generic bone morphologies as reported, for example, in Otolaryngology, and maxillofacial and cranial reconstructive surgery. 4 Fracture simulations with 3D models 5 can already replace plastic bones for training of osteosynthesis as illustrated in Figure 3. Exercising preoperative planning on a generic 3D environment will permit the trainee to gain a more a comprehensive understanding of the pertinent bone's morphology.…”
Section: Discussionmentioning
confidence: 99%
“…However, these models are not suited for drilling, since the material is solid plastic. We employed SLS and found that our model allows easy drilling and is suited for dissection practice [1].…”
Section: Discussionmentioning
confidence: 99%
“…The other is a model of the osseous labyrinth created using the data extracting the radiolucent area. The conventional surgical drill and instruments were used to dissect and trim the model as previously reported [1].…”
Section: Methodsmentioning
confidence: 99%
“…This temporal bone model was originally intended for anatomical study and surgical training in the field of otology. 11,12) Otological surgery of the temporal bone is mostly limited to inside the bone. In contrast, neurosurgical skull base surgery involves dissection of the dura mater and The periosteal layer of the dura mater was modeled with yellow silicone, and the dural sinuses with blue silicone.…”
Section: Introductionmentioning
confidence: 99%